Summer's storm - Domning, Denise (Australia A Topaz Book, 1994)
In a world where folk are either common or noble, Temric FitzHenry, bastard of Graistan, is neither and both. Only too late does he meet his equal, Philippa of Lindurst, also a bastard raised to noble expectations; Philippa is already married. When Temric discovers the abuse Philippa endures, his heart demands that he steal her from her husband. As he does so, he promises that shell never know pain with him. Philippa cherishes each day she spends with him, knowing her husband will someday find them and they will die. If Temric is ever to be truly hers, Philippa must find the courage to defy death and escape a heritage that makes her love of Temric the deepest of sins. Set in the late twelfth century, Summers Storm takes place in the time of King Richard the Lionheart and Robin Hood.
Keywords: Great Britain